Rescue of Primary Incomplete Microkeratome Flap with Secondary Femtosecond Laser Flap in LASIK - E. A. Razgulyaeva (Case Reports in Ophthalmological Medicine)
For laser-assisted in situ keratomileusis (LASIK) retreatments with a previous unsuccessful mechanical microkeratome-assisted surgery, some surgical protocols have been described as feasible, such as relifting of the flap or the creation of a new flap and even the change to a surface ablation procedure (photorefractive keratectomy (PRK)). This case shows the use of femtosecond technology for the creation of a secondary flap to perform LASIK in a cornea with a primary incomplete flap obtained with a mechanical microkeratome. As we were unable to characterize the interface of the first partial lamellar cut, a thick flap was planned and created using a femtosecond laser platform. As the primary cut was very thick in the nasal quadrant, a piece of loose corneal tissue appeared during flap lifting which was fitted in its position and not removed. Despite this condition and considering the regularity of the new femtosecond laser cut, the treatment was uneventful. This case report shows the relevance of a detailed corneal analysis with an advanced imaging technique before performing a secondary flap in a cornea with a primary incomplete flap. The femtosecond laser technology seems to be an excellent tool to manage such cases successfully.